The Urgency of the Indonesian Doctors Association in Providing Recommendations for Doctors' Practice Licenses (Law No. 29 of 2004 and Law No. 17 of 2023 - Liwandika, Galang; Rizka, Rizka; Soekiswati, Siti (IHSA Institute, 2024)
Medical practice is a series of activities carried out by doctors and dentists on patients as part of their medical practice. When practicing medicine, a doctor who practices medicine or provides medical services must meet the requirements set by the government. All doctors and dentists who practice medicine must have a Practice License. New doctors can practice if they already have STR and SIP. This research aims to analyze the urgency of IDI's role in providing recommendations for registration of medical practice permits and its legal aspects. This research uses normative research. The results of this research explain that there are differences in SIP registration for doctors, namely: In Law no. 29 of 2004 IDI has a role and authority in providing recommendations. Meanwhile, Law No. 17 of 2023 states that registration of a doctor's SIP no longer requires a doctor's recommendation but only an STR and place of practice. The elimination of IDI's authority as a professional organization for doctors means that IDI loses its role in supervising the development and improvement of the quality of doctors to ensure that doctors who have SIP are doctors who are competent in their field